2020
DOI: 10.2399/ana.20.002
|View full text |Cite
|
Sign up to set email alerts
|

Occipital emissary foramina in human skulls: review of literature and proposal of a classification scheme of the occipital venous anastomoses in the posterior cranial fossa

Abstract: Objectives: The present study aims to explain the interesting discrepancy between the occipital emissary foramina and the respective emissary veins in the literature. Majority of the studies report that the foramina have a low and variable frequency, but the emissary veins are reported to be disproportionately present in quite large number of patients in some diagnostic imaging studies. Methods: Seventy-five adult skulls were examined for the presence of occipital foramina. Results: A complete occipital emissa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 4 publications
0
5
3
Order By: Relevance
“…25 As far as EOC is concerned, in the present study, OEF was found in 3 skulls on EOC and on both sides of EOC in 3 skulls constituting 3.75% which is lower than that detected by Alghamdi et al 25 Single OEF was found on the left side of EOC at a distance of 9 mm from the border of the foramen magnum in 1.33% of skulls. 17 In the present study, a single OEF was detected on the left side of EOC in 4 skulls, constituting 5% which is higher than the above study.…”
Section: Resultscontrasting
confidence: 72%
See 4 more Smart Citations
“…25 As far as EOC is concerned, in the present study, OEF was found in 3 skulls on EOC and on both sides of EOC in 3 skulls constituting 3.75% which is lower than that detected by Alghamdi et al 25 Single OEF was found on the left side of EOC at a distance of 9 mm from the border of the foramen magnum in 1.33% of skulls. 17 In the present study, a single OEF was detected on the left side of EOC in 4 skulls, constituting 5% which is higher than the above study.…”
Section: Resultscontrasting
confidence: 72%
“…The incidence of OEF in the present study is higher than that observed by Kadanoff and Mutafov 15 in Bulgarian skulls and by Sharma et al 16 in Indian skulls but lower than that detected by Subashri and Thenmozhi 14 . Variability in the incidence of this foramen was because some investigators designated all openings on occipital bone as OEF irrespective of their patency 17 . Only patent foramina transmit emissary veins, and so do true OEF 17 .…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations